Prevalence of partial edentulism and RPD design in patients treated at College of Dentistry, Imam Abdulrahman Bin Faisal University, Saudi Arabia - Mohammed M. Gad; Reem Abualsaud; Ahmad M. Al-Thobity; Khalid S. Al-Abidi; Soban Q. Khan; Mohamed S. Abdel-Halim; Fahad A. Al-Harbi; Mai El Zayat; Shaimaa M. Fouda (Elsevier, 2020)
This study aimed to investigate the prevalence of partial edentulism, RPD type, design, and components and their frequency of use by patients at the prosthodontic clinics of the College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia. The prepared surveys, laboratory authorization forms, and images of the RPD metal frameworks on casts were used for data collection. Two calibrated investigators studied the digital photographs to identify the Kennedy classification, type of RPD, major connector, clasp assembly, and other details. Data was collected and analyzed statistically. The results showed that the most common class of partial edentulism was Kennedy class I, whereas class IV was the least (p < 0.001). Sixty two percent of fabricated RPDs had metal frameworks, whereas 37.2% were frameless. RPI was the most frequently used clasp assembly (38.9%), a significant finding in Kennedy class I(p < 0.01). The maxillary anteroposterior palatal strap and mandibular lingual plate were the most commonly used major connectors, at 41.2% and 60.8%, respectively. Conclusions: Simple RPD design that accomplishes the treatment objectives as well as proper communication with a well-trained dental technician would promote the success of RPDs. Keywords: Direct retainer, Kennedy classification, Major connector, Partial edentulism, Removable partial denture